Spatio-temporal tourism land use changes: A case study of a typical tourism district in Song County, China - Huanhuan Li; Merimkul Kerimkulova; Shuman Wang; Jinlong Cheng; Weige Zhang (Tourism)
The research aims to analyse the spatial and temporal changes in tourism land use based on the example of a typical region and to substantiate the possible environmental, economic, socio-cultural and other types of consequences of such modifications. The study was conducted using methods of cognition: system analysis, synthesis, specification, generalisation, abstraction, deduction and formalisation. Based on the research results, potential spatial and temporal changes in those territories involved in tourism activities were identified, the peculiarities of the dynamics and directions of such changes were analysed, and the most influential factors and methods of management identified. In addition, possibilities for resolving the consequences are studied and the effectiveness of risk management assessed. The practical significance of the results obtained lies in the opportunity to apply them to the process of forming decisions for tourism land use activities and further management of tourism processes. An effective analysis of spatial and temporal changes in a typical tourism district can serve as a guide for rational planning of tourism activities.